Secrets of sound studying the calls and songs of whales, elephants, and birds - Sayre, April Pulley (Boston : Houghton Mifflin, 2002)
Examines the work of several bioacousticians, scientists who study the sounds made by living creatures, discussing the results and importance of their research.
Includes bibliographical references (p. 60) and index.
All Ages.
Keywords: Bioacoustics -- Juvenile literature; Animal sounds